Modelling The Trade Flows of The Gulf Cooperation Council Countries: A New Approach to Gravity Model - Aysu Insel; Mehmet Mahmut Tekçe (Turkish Economic Association, 2009)
This study analyzes the trade flows of the Gulf Cooperation Council (GCC) both among its member countries and with the rest of the world by employing a panel data gravity model in the context of the single country approach in order to capture the impacts of observable and unobservable variables on the bilateral trade flows for the 1997-2002 and 2003-2007 periods. In this paper, the research question is whether the trade flows of each GCC countries with its partners have sustained and/or they have developed new relations over time, mainly after 2003 custom union agreement of the GCC. For this purpose, fixed effects models have been estimated in order to obtain individual country effects variable. Then, trade model- as a function of distance and income variables- with the country effects model- as a function of the time invariant control variables- have been estimated simultaneously within the panel data analysis using the Least Squares and Generalised Method of Moments under the assumption of the presence of cross section heteroskedasticity and the robust standard errors. There are three contributions of this paper: (1) Examination of bilateral trade flows for each GCC country over the two different sample periods. (2) Country ranking for each GCC country over the two different sample periods. (3) Simultaneous gravity model specification for each GCC country over the two different sample periods.
Keywords: 330; Gulf Cooperation Council Countries; Trade Flows; Gravity model; Panel Analysis; System Estimation; Internationale Wirtschaftsbeziehungen; Arabische Golf-Staaten